Enhancing Digital Literacy for Young Learners: Pengenalan Teknologi Digital dan Bahasa Inggris untuk Siswa PAUD dan TK - Tri Pujiani; Soali, Muhammad; Ida Dian Sukmawati (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
This community service program aims to enhance digital literacy among young children through interactive and educational activities. The program includes the introduction of basic technology, such as the use of computers and related devices, as well as the development of children's vocabulary through images, stories, and games. Additionally, the program focuses on improving speaking and listening skills, encouraging children to actively speak and listen attentively. The introduction of digital storytelling plays a key role in building children's imagination and fostering an interest in both technology and books. Furthermore, the program seeks to cultivate a love for reading by introducing picture books, both in physical and digital formats. Through this approach, it is expected that children will be better prepared for the digital era and develop essential skills for their daily lives